Resveratrol aggravated H2O2-induced the HK-2 cell damage by inhibiting AKT phosphorylation - Shicheng Luo; Yuning Chen; Xuyi Ma; Feng Tian; Xiaozhou He (PLoS ONE, 2025)
Aims Reactive oxygen species (ROS) can induce renal damage when renal ischemia-reperfusion occurs as a result of factors such as renal transplant and shock. It is well established that oxidant damage plays an important role in the mechanism of ischemia-reperfusion. Resveratrol (RSV) is known for its antioxidant properties. However, in our investigations we found that RSV could aggravate human proximal tubular cells (HK-2 cells) damage when exposed to H2O2. Consequently, our findings suggested that RSV may potentially aggravate renal damage in the context of renal ischemia-reperfusion. Methods CCK-8 reagent kits were utilized to assess cell proliferation. Western blot analysis was employed to determine the expression level of protein about γ-H2ax, PTEN, AKT, P-AKT and Cleave-caspase3. Additionally, the process of apoptosis was examined using flow cytometry. Result The CCK-8 assays results revealed a dose-dependent inhibition of cell proliferation when HK-2 cells were exposed to varying concentrations of H2O2. Furthermore, when HK-2 cells were cultured with 250uM H2O2 and different concentrations of RSV, the CCK-8 results indicated a significant reduction in HK-2 cell viability with increasing RSV dosage. Flow cytometry analysis of HK-2 cells exposed to 250uM H2O2 and 10uM RSV demonstrated that RSV exacerbated apoptosis in H2O2-induced HK-2 cells. Western blot analysis revealed that RSV inhibited the expression of P-AKT and exacerbated damage to H2O2-induced HK-2 cells. Subsequently, we selected 10uM MK for further investigation, with CCK-8 results showed a significant reduction in HK-2 cell viability when the AKT phosphorylation process was inhibited by MK. Western blot analysis indicated that the cleave-caspase-3 was further activated when the AKT phosphorylation process was inhibited by MK. Flow cytometry demonstrated a significant increase in the apoptosis of HK-2 cells when the AKT phosphorylation process was inhibited by MK. In the case of P-AKT overexpression, Western blot analysis showed a significant increase in P-AKT expression, while a significant decrease in cleave-caspase-3. Flow cytometry revealed a significant decrease in the apoptosis of HK-2 cells. Finally, Western blot analysis demonstrated a decrease in P-AKT levels along with the expression of PTEN. Conclusions Our research substantiated that RSV could aggravate H2O2 induced HK-2 cells damage by upregulating the expression of PTEN and inhibiting AKT phosphorylation. It suggested that RSV may deteriorate renal damage in the context of renal ischemia-reperfusion injury.